دراسة حالة ارتفاع الجهد للمولدات المتواقتة في المحطة الحرارية لمصفاة بانياس - بدر زيد (Latakia University Journal -Engineering Sciences Series, 2019)
درسنا الحالة غير الطبيعية لارتفاع الجهد للمولدات المتواقته في المحطة الحرارية بمصفاة بانياس وتبين أن ذلك لا يعود للظروف الاستثمارية فقط وإنما يتعلق بالناحية التصميمية لهذه المولدات أيضاً ، لا سيما من حيث نسبة الدارة القصيرة (S.C.R) . يعتبر نزع الحمولة الفجائي عن هذه المولدات السبب الأساسي لارتفاع الجهد على أقطابها ، إذ تم تحديد هذا النزع بطريقتين : الأولى : بوساطة التغيير القسري للعزم الخارجي للمولد المتواقت(تغيير في كمية البخار الداخلة إلى التوربين لسبب ما) والثانية بوساطة نزع حمولة بعض المغذيات الفجائي لسبب ما ، فقد تم رسم منحنيات وتشكيل جداول تغطي هذه الأسباب. في نهاية البحث تم اقتراح حلول عملية من شأنها التخفيف قدر الإمكان من احتمال ارتفاع الجهد عند نزع الحمولات الفجائي بهاتين الطريقتين . In the present work, reasons for the voltage rise in the synchronous Banias refinery thermal power station are studied. These reasons are not only due to the investment reasons, but to the designing of these generators which is related to the short-circuit (S.C.R). Sudden load removing–off these generators could be considered as the main reason of that voltage-rise on its poles. This could be determined by two methods: firstly by the Sudden variation of an external torque of the synchronous generator load, and secondly by the load removing of some Sudden feeding. Formation tables covering analysis of these reasons are drawn. My research concludes with recommending some experimental solutions to reduce the voltage-rise possibility during the Sudden load withdrawing using the above two mentioned methods .